In Vino Pecunia? The Association Between Beverage-Specific Drinking Behavior and Wages - Nicolas R. Ziebarth; Markus M. Grabka (Journal of Labor Research, 2009)
The positive association between moderate alcohol consumption and wages is well documented in the economic literature. Positive health effects as well as networking mechanisms serve as explanations for the “alcohol–income puzzle.” Using individual-based microdata from the SOEP for 2006, we confirm that this relationship exists for Germany as well. More importantly, we shed light on the alcohol–income puzzle by analyzing, for the first time, the association between beverage-specific drinking behavior and wages. In our analysis, we disentangle the general wage effect of drinking into diverse effects for different types of drinkers. Mincerian estimates reveal significant and positive relationships between wine drinkers and wages as well as between multiple beverage drinkers and wages. When splitting the sample into age groups, the “drinking gain” disappears for employees under the age of 35 and increases in size and significance for higher age groups. We also find a “beer gain” for the oldest age group and male residents of rural areas as well as a “cocktail gain” for residents of urban areas. Several explanations for our empirical results are discussed in view of the likelihood that the alcohol–income puzzle is a multicausal phenomenon.
Additional information: The original publication is available at www.springerlink.com: http://dx.doi.org/10.1007/s12122-009-9064-7
Keywords: I10; I12; J31; J30; 330; Alcohol–income puzzle; Beverage-specific drinking behavior; Wages; Wine; Socio-Economic Panel Study (SOEP); Alkoholkonsum; Lohnstatistik; Panel; Deutschland